2020
DOI: 10.3390/antiox9080709
|View full text |Cite
|
Sign up to set email alerts
|

The Versatility of Antioxidant Assays in Food Science and Safety—Chemistry, Applications, Strengths, and Limitations

Abstract: Currently, there is a growing interest in screening and quantifying antioxidants from biological samples in the quest for natural and effective antioxidants to combat free radical-related pathological complications. Antioxidant assays play a crucial role in high-throughput and cost-effective assessment of antioxidant capacities of natural products such as medicinal plants and food samples. However, several investigators have expressed concerns about the reliability of existing in vitro assays. Such concerns ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
275
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 288 publications
(290 citation statements)
references
References 105 publications
(230 reference statements)
9
275
1
5
Order By: Relevance
“…Detailed analysis of the obtained results revealed some structure–antioxidant activity relationships related to certain antioxidant mechanisms. In accordance with Sadeer et al [ 16 ], FRAP is based on an electron transfer mechanism in which aryloxyl radicals are formed. In the presented studies, the highest reduction activity was observed for cyclic hydrocarbon terpenes with conjugated double bonds without single electron transfer (SET) moiety characteristics (with the exception of γ-terpinene without the moiety) ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 66%
“…Detailed analysis of the obtained results revealed some structure–antioxidant activity relationships related to certain antioxidant mechanisms. In accordance with Sadeer et al [ 16 ], FRAP is based on an electron transfer mechanism in which aryloxyl radicals are formed. In the presented studies, the highest reduction activity was observed for cyclic hydrocarbon terpenes with conjugated double bonds without single electron transfer (SET) moiety characteristics (with the exception of γ-terpinene without the moiety) ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 66%
“…For example, in the Folin–Ciocalteu method, the reagent could be reduced by not only phenolics but also non-phenolics (peptides etc. ), and thus the obtained results might not be reliable [ 24 , 25 ]. In this sense, advanced chromatographic techniques are helpful to provide certain information regarding the chemical profiles of plant extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these assays has unique properties and limitations, making it difficult to compare results generated using different methods—for example, measurement at a fixed time or kinetic, measurement of different concentrations or only one concentration, and the use of different solvents [ 23 , 24 , 25 , 26 ]. Furthermore, the outcome of the assays can be evaluated in different ways, resulting in metrics, such as half maximal effective concentration (EC 50 ), time to reach the EC 50 (T EC 50 ), antiradical efficiency, antiradical power (ARP), stoichiometry, kinetic behavior and rate constant, radical scavenging activity, or trolox equivalent antioxidant capacity (TEAC) [ 23 , 24 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%